ANALISIS HASIL TREATMENT PLANNING SYSTEM TEKNIK PENYINARAN 3D CONFORMAL RADIOTHERAPY DENGAN 2 VARIASI 5 ARAH LAPANGAN RADIASI YANG BERBEDA PADA KASUS KANKER PROSTAT DI RSUPN DR. CIPTO MANGUNKUSUMO - Arif Jauhari; Devi Octaviana Resma Pamungkas; Prabaningtyas Widya Dewi (Dian Nuswantoro Semarang, 2019)
Prostate cancer is a cancer or malignant tumor that develops in the prostategland. This gland is located under the male bladder as a function of removingand storing a type of fluid that produces semen. After a man aged 50 years,usually the prostate will gradually enlarge. Prostate enlargement in old age isnormal.To compare the results of TPS (treatment planning system) 3D CRT (ConformalRadiotherapy) irradiation techniques with 2 different 5-way radiation fieldvariations in cases of prostate cancer based on the dose received by the targetvolume, organ at risk and isodose curve.The type of research used in this study is a type of qualitative analysis. The placeof research was conducted at the radiotherapy installation at RSUPN Dr. CiptoMangunkusumo. The time of research applies from March to May 2017.From the results of the study, without optimization in the treatment planningsystem during planning, it was seen in the organ at risk of bladder, caput femurisdextra and the caput femuris sinistra received fewer doses using planning A(gantry angle: 00, 750, 1450, 2250, 2850).Planning A (gantry angle: 00, 750, 1450, 2250, 2850) is better for volume targetsand organ at risk such as bladder, caput femuris dextra dan caput femurissinistra.Keywords: Prostate cancer, TPS (treatment planning system), 3D CRT(Conformal Radiotherapy)